Long-term effects of wildfire smoke exposure during early life on the nasal epigenome in rhesus macaques. (January 2022) - Brown, Anthony P.; Cai, Lucy; Laufer, Benjamin I.; Miller, Lisa A.; LaSalle, Janine M.; Ji, Hong
Graphical abstract: Highlights: Early life wildfire smoke exposure was associated with epigenetic changes in macaques. Many of the DNA methylation changes occurred near nervous and immune system genes. Genes involved in asthma, COPD, and IPF showed changes in DNA methylation. Genomic locations with DNA methylation changes were enriched for bivalent markers. FLOT2 showed reduced expression levels in exposed macaques. Abstract: Background: Wildfire smoke is responsible for around 20% of all particulate emissions in the U.S. and affects millions of people worldwide. Children are especially vulnerable, as ambient air pollution exposure during early childhood is associated with reduced lung function. Most studies, however, have focused on the short-term impacts of wildfire smoke exposures. We aimed to identify long-term baseline epigenetic changes associated with early-life exposure to wildfire smoke. We collected nasal epithelium samples for whole genome bisulfite sequencing (WGBS) from two groups of adult female rhesus macaques: one group born just before the 2008 California wildfire season and exposed to wildfire smoke during early-life (n = 8), and the other group born in 2009 with no wildfire smoke exposure during early-life (n = 14). RNA-sequencing was also performed on a subset of these samples. Results: We identified 3370 d ifferentially m ethylated r egions (DMRs) (difference in methylation ≥ 5%, empirical p < 0.05) and 1 differentially expressed gene ( FLOT2 ) (FDR < 0.05, fold of change ≥ 1.2). The DMRs were annotated to genes significantly enriched for synaptogenesis signaling, protein kinase A signaling, and a variety of immune processes, and some DMRs significantly correlated with gene expression differences. DMRs were also significantly enriched within regions of bivalent chromatin (top odds ratio = 1.46, q-value < 3 × 10 -6 ) that often silence key developmental genes while keeping them poised for activation in pluripotent cells. Conclusions: These data suggest that early-life exposure to wildfire smoke leads to long-term changes in the methylome over genes impacting the nervous and immune systems. Follow-up studies will be required to test whether these changes influence transcription following an immune/respiratory challenge.